Matching Skills of Individuals and Firms Along the Career Path - Elisabeth Bublitz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper presents an analytical setup that makes predictions for the relationships between firm and occupation specific human capital and job switches. The predictions are then tested using the task based approach. The results, based on data for Germany, show that the degree to which firm knowledge is portable depends on skill similarities between the firms. In case of job switches, less experienced workers travel longer skill distances between firms than more experienced workers. Firm and occupational skill distances, that is firm and occupation specific knowledge, both are negatively related to wages in a new job, although the relative importance differs by qualification level. The share of workers in the same occupational group within the firm, occupational intensity, can reflect switching motivations of workers. Occupational intensity decreases with experience and is negatively associated with wages.
Keywords: J24; J62; J31; 330